Application of carbon isotope chemostratigraphy to the Renison dolomites, Tasmania: a Neoproterozoic age - Adabi, MH (1997)
This study uses carbon isotope chemostratigraphy to propose an age for the Success Creek Group and Crimson Creek Formation in the absence of any direct radiometric dates, palaeomagnetic or reliable palaeontological data. The δ13C values were determined for the least-altered dolomite samples. Suitable samples were selected on the basis of grainsize, cathodoluminescence petrography, most enriched δ18O values ( > -2‰) low Mn/Sr ratios and low Fe and Mn concentrations. The average least-altered, most 13C-enriched dolomicrite samples in the youngest (No. 1) dolomite horizon are + 4.6‰. This is typical of Neoproterozoic (but not Cambrian) carbonates. The δ13C values of all dolomite samples in the succession are significantly positive (up to + 7.5‰) and the excursion characteristic of the Proterozoic/Cambrian boundary has not been observed. The lack of negative δ13C values in all dolomite samples studied also suggests an absence of correlatives of Sturtian and Varanger tillites in the dolomite successions. The δ13C values in all three dolomite horizons suggest a Neoproterozoic age between about 820 to 570 Ma (Cryogenian to Neoproterozoic III) on the current global compilation carbon isotope curves. This age for the Success Creek Group and Crimson Creek Formation, inferred from carbon isotope chemostratigraphy, can be substantiated by other evidence. The age of the Renison dolomites is constrained by K-Ar dates of 708 ± 6 Ma from detrital muscovite in the underlying Oonah Formation and 588 ± 8 and 600 ± 8 Ma from doleritic rock in a lithostratigraphic equivalent of the Crimson Creek Formation from the Smithton Basin. Furthermore, acritarchs and the stromatolite Baicalia cf. B. burra also suggest a Neoproterozoic rather than Cambrian age.